Corksorb enhances alkane degradation by hydrocarbonoclastic bacteria - Martins, Valdo R. (2021)
Biosorbent materials are effective in the removal of spilled oil from water, but their effect on hydrocarbonoclastic bacteria is not known. Here, we show that corksorb, a cork-based biosorbent, enhances growth and alkane degradation by Rhodococcus opacus B4 (Ro) and Alcanivorax borkumensis SK2 (Ab). Ro and Ab degraded 96 ± 1% and 72 ± 2%, respectively, of a mixture of n-alkanes (2 g L1) in the presence of corksorb. These values represent an increase of 6 and 24%, respectively, relative to the assays without corksorb. The biosorbent also increased the growth of Ab by 51%. However, no significant changes were detected in the expression of genes involved in alkane uptake and degradation in the presence of corksorb relative to the control without the biosorbent. Nevertheless, transcriptomics analysis revealed an increased expression of rRNA and tRNA coding genes, which confirms the higher metabolic activity of Ab in the presence of corksorb. The effect of corksorb is not related to the release of soluble stimulating compounds, but rather to the presence of the biosorbent, which was shown to be essential. Indeed, scanning electron microscopy images and downregulation of pili formation coding genes, which are involved in cell mobility, suggest that cell attachment on corksorb is a determinant for the improved activity. Furthermore, the existence of native alkane-degrading bacteria in corksorb was revealed, which may assist in situ bioremediation. Hence, the use of corksorb in marine oil spills may induce a combined effect of sorption and stimulated biodegradation, with high potential for enhancing in situ bioremediation processes. © Copyright © 2021 Martins, Freitas, Castro, Silva, Gudiña, Sequeira, Salvador, Pereira and Cavaleiro.